Hip joint load and muscle stress in soccer inside passing - Dupré, T.; Mortensen, K. R. L.; Lysdal, F. G.; Funken, J.; Müller, R.; Braun, M.; Krahl, H.; Kersting, U.; Potthast, W. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Studies investigating the mechanisms of adductor injuries in soccer have concentrated on full effort kicks. Purpose of this study was a kinetic analysis of the inside pass. Using infrared cameras and inverse dynamics, hip joint moments and adductor muscle stress was calculated during the swing phase of the pass. Moments in the transverse plane were nearly as high as in full effort kicks reported previously. Muscle stress in the m. gracilis reached up to 450 kPa. Considering the repetitive nature of inside passes in modern soccer, adductor muscles undergo high loads in matches and training. This might contribute to the explanation of the high incidences of adductor injuries. Practitioners should therefore consider the load-recovery-relation even in inside pass training. Specific strength training programs for the adductor and abductor muscle groups should be developed. CONCLUSION; High hip joint loads, in the transverse plane in particular, coupled with high stresses in the adductor muscles during submaximal inside passes might explain the high rates of groin injuries in football. Thus, it is important for practitioners, to dose pass training carefully, especially in kids and adolescent groups. Furthermore, those muscles might need isolated training.